Uji Kinerja dan Implementasi Aplikator Pupuk Cair Berbasis Variable Rate Application untuk Tanaman Kedelai (Glycine max) - Miraj Fuadi; Lilik Sutiarso; Radi Radi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Provision of fertilizer is crucial for improving the quality and quantity of the yield. However, using chemical fertilizer continuously with increasing doses can disrupt the balance of land nutrients. Therefore, it is necessary to use a variable-rate liquid fertilizer device to control fertilizer dose required by the plant. The research aimed to evaluate the variable-rate liquid fertilizer performance. The fertilizier applicator characterized by effective field capacity (EFC), theoretically field capacity (TFC) and field efficiency (FE). The materials used were fertilizier (Urea, Sp-36, KCL), Glycine max seeds Grobogan variety. While the equipments were a set of variable-rate liquid fertilizer applicator, scale, rollmeter, analytic balance, multitester, and calipers. To observe the plant responses by fertilizer applicator, a demplot of 36 x 8 m2 was divided in 6 plots of 12 x 4 m2 (A1, A2, ... A6). The evaluation showed respectively the EFC, TFC and FE were 624 m2/h, 864 m2/h and 72.27%. The soybean growth showed that statistically the application of fertilizers using an applicator did not significantly affect plant height parameters but significantly affected the stem diameter, number of leaves and coverage area. Nevertheless, it was still found that soybean crop had different productivity, shown by a significance value of 0.028. Regression analysis with the fertilizer SP-36 (X2) variable on productivity obtained the function Y = -1.405.10-4 + 0.12X2 – 0.001X22 with an R2 of 0.581. Regression analysis with the fertilizer KCl (X3) variable on productivity obtained the function Y = -2.546.10-16 + 0.053X3 – 2.063.10-4 X32 with an R2 value of 0.701.